2006
DOI: 10.1007/s10534-005-6666-2
|View full text |Cite
|
Sign up to set email alerts
|

Age-associated Iron Accumulation in Bone: Implications for Postmenopausal Osteoporosis and a New Target for Prevention and Treatment by Chelation

Abstract: Iron accumulation in tissues is believed to be a characteristic of aged humans and a risk factor for some chronic diseases. However, it is not known whether age-associated iron accumulation is part of the pathogenesis of postmenopausal osteoporosis that affects approximately one out three women worldwide. Here, we confirmed that this accumulation of iron was associated with osteopenia in ovariectomized (OVX) rats (a model of peri- and postmenopausal osteoporosis due to estrogen deficiency). To further investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 23 publications
1
40
1
Order By: Relevance
“…Precious epidemiological studies have demonstrated that the postmenopausal women harbor a higher level of body iron than premenopausal women (Jian et al, 2009). Similar to clinical observations, Liu and his colleagues documented iron accumulation in the ovariectomized (OVX) rats, a model of postmenopausal osteoporosis (Liu et al, 2006). In contrast, a pilot study suggested that iron chelator could prevent bone loss induced by excess iron in OVX rats (G. Liu et al, 2008).…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…Precious epidemiological studies have demonstrated that the postmenopausal women harbor a higher level of body iron than premenopausal women (Jian et al, 2009). Similar to clinical observations, Liu and his colleagues documented iron accumulation in the ovariectomized (OVX) rats, a model of postmenopausal osteoporosis (Liu et al, 2006). In contrast, a pilot study suggested that iron chelator could prevent bone loss induced by excess iron in OVX rats (G. Liu et al, 2008).…”
Section: Introductionmentioning
confidence: 82%
“…The major reason for choosing this time point is because biological effects induced by estrogen deficiency need at least 4-6 weeks to be reflected in animals. For example, most studies in evaluating the ovariectomized models for postmenopausal osteoporosis are performed over 1 month after ovariectomy (G. Liu et al, 2006Liu et al, , 2008Sottile et al, 2004;Thompson et al, 1995). Considering iron metabolism upon certain chronic physiological alternation, the end-point of iron-related studies are normally set over 1 month after ovariectomy when using ovariectomized models (Ikeda et al, 2012;Liu et al, 2006;Mattace Raso et al, 2009).…”
Section: Elevated Hepcidin Expression In Liver Devoid Of Endogenous Ementioning
confidence: 99%
See 1 more Smart Citation
“…By searching for factor(s) other than estrogen deficiency in osteoporosis, we found that both dietary iron deficiency and overload affect bone in animal studies (8,18,19,21,23,29). One recent report showed that osteoporosis patients are slightly iron deficient, having lower serum iron and higher transferrin as compared with the control group (7).…”
Section: Iron and Osteoporosismentioning
confidence: 99%
“…Ovariectomized rats with an increased iron level showed a higher tendency to have osteoporosis (6). Tsay et al (7) reported that the iron overload (IO)-induced bone loss in mice was correlated with the inflammatory bone resorption and oxidative stress.…”
Section: Introductionmentioning
confidence: 99%